Cotinine Fluctuation in Maternal Saliva During and After Pregnancy: Implications for Perinatal Outcomes. Issue 5 (September 2021) - Gwon, Seok Hyun; Jeong, Suyong; Bullock, Linda
Abstract: Purpose: The purpose of this study was to determine maternal cotinine levels in saliva at the first (T-1) and third trimesters of pregnancy (T-2), and postpartum (T-3) among women who reported smoking a consistent number of cigarettes. The goal was to generate data to provide suggestions about how nurses can improve patient outcomes for women who smoke. Methods: Saliva cotinine values obtained from the randomized controlled trial (BabyBEEP) were used for this secondary analysis. We examined variations in saliva cotinine between the first and third trimesters of pregnancy and postpartum among light and heavy smokers. Cotinine values for pregnant smokers who were in the control group (not randomized to any intervention) and reported smoking the same range of cigarettes during and after pregnancy were used for the analyses ( n = 43). Descriptive statistics and repeated-measures ANOVA were used for analyses. Results: There were differences in maternal saliva cotinine levels across the different time points and between the groups. There was a significant interaction effect between time and group. Cotinine decreased from T-1 to T-2 in heavy smokers and increased from T-2 to T-3 among both light and heavy smokers. Cotinine at T-3 was higher than T-1 among light smokers. Clinical Implications: Findings support accelerated nicotine metabolism during pregnancy and need for smoking cessation efforts throughout pregnancy to help women stay smoke free during postpartum. Abstract : Smoking during pregnancy and postpartum can have a significant negative effect on mothers and babies. In this study, maternal cotinine (a byproduct of nicotine) levels in saliva at the first and third trimesters of pregnancy and postpartum among women who reported smoking a consistent number of cigarettes were studied. Findings support accelerated nicotine metabolism during pregnancy and need for smoking cessation efforts throughout pregnancy to help women stay smoke free at postpartum.